Attitudes toward vaccinations are becoming more polarized in New Zealand: Findings from a longitudinal survey - Lee, Carol H.J. (EClinicalMedicine, 2020)
BACKGROUND: Despite continuing vaccine controversies, little is known about the trajectory of change in vaccine confidence over time. The current study examined whether there are subpopulations among the New Zealand public with diverging trajectories of confidence in the safety of childhood vaccinations from 2013 to 2017. METHODS: Using longitudinal survey data from the New Zealand Attitudes and Values Study, latent class growth models identified subpopulations with distinct rates and directions of change in vaccine confidence from 2013 to 2017 (N= 12,423; 11,912; 12,009; 10,254). The demographic profiles of these subpopulations were examined. FINDINGS: Most New Zealanders’ (60%) maintained strong vaccine confidence throughout the years (i.e. vaccine believers), but 30% expressed decreasing confidence over time (i.e. vaccine skeptics). Around 10% were former skeptics who had low vaccine confidence in 2013 but showed increasing confidence thereafter. Men, Europeans/Others, those more educated and living in more affluent regions were more likely to be vaccine believers. Relative to former skeptics, women, older individuals and those with lower education were more likely to be vaccine skeptics. INTERPRETATION: Attitudes toward the safety of childhood vaccinations are becoming increasingly polarized in New Zealand. Roughly 30% of the population are becoming more concerned about vaccine safety over time, 10% are becoming more confident, whereas 60% show consistent high vaccine confidence. It is vital to further investigate the key contributors to decreasing confidence among vaccine skeptics and implement target interventions. FUNDING: Templeton Religion Trust Grant (TRT0196) for data collection; Corresponding author supported by University of Auckland Doctoral Scholarship.